2022
DOI: 10.1021/acs.biochem.1c00749
|View full text |Cite
|
Sign up to set email alerts
|

Double Mutant of Chymotrypsin Inhibitor 2 Stabilized through Increased Conformational Entropy

Abstract: The conformational heterogeneity of a folded protein can affect not only its function but also stability and folding. We recently discovered and characterized a stabilized double mutant (L49I/I57V) of the protein CI2 and showed that state-of-the-art prediction methods could not predict the increased stability relative to the wild-type protein. Here, we have examined whether changed native-state dynamics, and resulting entropy changes, can explain the stability changes in the double mutant protein, as well as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Protein flexibility was investigated with biochemical experiments and related to protein function . The influence of mutations on conformational entropy is another line of research . Conformational entropy in proteins was related to intrinsic structural disorder, folding, and binding .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein flexibility was investigated with biochemical experiments and related to protein function . The influence of mutations on conformational entropy is another line of research . Conformational entropy in proteins was related to intrinsic structural disorder, folding, and binding .…”
Section: Introductionmentioning
confidence: 99%
“…27 The influence of mutations on conformational entropy is another line of research. 28 Conformational entropy in proteins was related to intrinsic structural disorder, folding, and binding. 29 Deliberations on conformational entropy, and protein dynamics in general, being slaved to water appear in refs 30 and 31.…”
Section: Introductionmentioning
confidence: 99%
“…The most affected regions are clustered at the N-terminal end of the two main b-strands and in the inhibitory loop. These areas of CI2 already stood out as exchange outliers in our recent analysis of the fast dynamics in CI2 10 . The present analysis provides more details about the thermodynamics, and kinetics of this slow process, as well as the structures of the involved states.…”
Section: Discussionmentioning
confidence: 92%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 22, 2022. ; https://doi.org/10.1101/2022.12.21.521530 doi: bioRxiv preprint Our analysis of the fast sub-nanosecond dynamics revealed that CI2 also experiences conformational dynamics on the ms time scale, but from that work we could not extract any details about the slow process 10 . In the present work, we asked what the characteristics of the slow conformational process are and if this might help rationalize some of the stabilizing effect in the L49I/I57V variant of CI2.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation